Castleman disease: Case series of two surgical patients from different ends of the disease spectrum with literature review - C.G., Radhika Raj (Int J Surg Case Rep, 2018)
Castleman Disease (CD) is a rare, heterogeneous group of hyperimmune lymphoproliferative disorders, not very familiar to surgeons. Unicentric Castleman Disease (UCCD) at one end of the spectrum is a localized disease, with little or no systemic symptoms. It may be an incidental radiological finding or detected while investigating for a symptomatic lymph node mass. Surgery is the primary treatment and has good long term prognosis. Multicentric Castleman Disease (MCCD) is a more serious systemic condition, often associated with constitutional symptoms. Exaggerated systemic inflammatory response secondary to “Cytokine storm” involving Interleukin-6 (IL-6) may cause multi-organ dysfunction. In addition, immunosuppression or malignant transformation can prove lethal. Human Herpes Simplex Virus 8 (HHV8) associated MCCD is a major subgroup occurring in immunocompromised individuals due to the viral trigger. Antiviral therapy is important in its treatment. Idiopathic MCCD (IMCCD) has no known biomarker and is diagnosed after excluding infective, autoimmune and malignant conditions of lymphoid tissue. IMCCD requires systemic therapy. We report a patient of UCCD who presented as a retroperitoneal mass in right iliac fossa causing pressure on femoral nerve. Following successful surgical excision she had good recovery. We report another patient who had large inguinal lymph node mass with constitutional symptoms. IMCCD was diagnosed after excision biopsy and comprehensive work up. Patient was started on corticosteroids followed by CD-20 targeted therapy. These two cases showcase the two ends of the clinical spectrum of CD requiring different management protocols. Awareness among surgeons and diligent work-up is imperative for early diagnosis and best outcome.